Anti-Discrimination Laws and Work in the Developing World: A Thematic Overview - Fredman, Sandra (World Bank, Washington, DC, 2013)
This paper reviews legal and other instruments aimed at addressing labor market discrimination in developing countries in the context of understanding jobs as the connection between the three identified transformations at the center of economic development: living standards, productivity gains, and social cohesion. Discrimination impacts living standards by excluding individuals from the labor market, by (1) consigning them to low paid, low quality, or insecure jobs; (2) subjecting them to victimization, violence, harassment, or violence; or (3) inhibiting their opportunities to benefit from promotions, training, or personal development, because of their gender, race, ethnicity, sexual orientation, age, or disability. Discrimination hinders productivity by excluding potentially productive workers from the workforce and failing to capitalize on their full potential. It can also have serious consequences for social cohesion, whether in its explicit forms of hatred, prejudice, violence, and harassment, or in its more insidious forms of condemning certain groups to low quality jobs, joblessness, or job insecurity. Beyond the labor market, discrimination in education prevents individuals from achieving their potential and contributing to a productive and cohesive society, while bias in property, marriage, and personal laws make it impossible to enter the paid labor force on equal terms. The current report discusses de jure equality and anti-discrimination laws—and their implementation (including affirmative action)—in the formal and informal sectors.